Differentiated Instruction in ELT: Indonesian Pre-Service and In-Service Teachers’ Capabilities, Strategies, and Barriers - Musyarrofah, Hamdatul; Kurniawati, Adelia Almira; Asad, Ahmad Sidiq Al; Fadlillah, Anam (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
This study examines how the capabilities and the strategies of pre-service and in-service teachers in applying DI in their classroom as well as the barriers to that application. A descriptive qualitative study was employed through questionnaire distribution to thirty-six pre-service and in-service teachers and interviews with four in-service teachers. The data were analyzed by using descriptive statistics and thematic analysis. Results show that in-service teachers gained a higher level of capability in DI implementation rather than pre-service teachers. Hence, pre-service teachers need more understanding and practices of DI in the lecture and teaching practicum. Diverse strategies were implemented by the teachers, such as flipped classrooms, creating diverse forms of materials, outdoor learning, etc. Several barriers were also experienced by the teachers including limited time of learning, diverse materials and rubric preparation, and lack of facilities. The barriers related to content, process, product, and learning style can be solved by other teachers’ strategies addressed, for instance adapting materials and flipped classrooms.